1998
DOI: 10.1074/jbc.273.38.24583
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Spectral Tuning in Blue Cone Visual Pigments

Abstract: Spectral tuning by visual pigments involves the modulation of the physical properties of the chromophore (11-cis-retinal) by amino acid side chains that compose the chromophore-binding pocket. We identified 12 amino acid residues in the human blue cone pigment that might induce the required green-to-blue opsin shift. The simultaneous substitution of nine of these sites in rhodopsin (M86L, G90S, A117G, E122L, A124T, W265Y, A292S, A295S, and A299C) shifted the absorption maximum from 500 to 438 nm, accounting fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
81
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(88 citation statements)
references
References 48 publications
(59 reference statements)
6
81
1
Order By: Relevance
“…However, the mutant pigment at pH 4.4, 4.8, 5.5, 6.2, 6.4, 6.6, 7.2, 7.5, 7.8, 8.6, and 11.4 shows identical absorption spectrum to that at pH 6.6 (results not shown). Thus, the various levels of acid treatment suggest that there is no change in its protonation state that influences the electrostatic environment of the chromophore (26). At present, it is not clear why the absorption spectrum of the mutant pigment is broader than that of the UV pigment.…”
Section: Molecular Evolution Of the Avian Uv Pigments: Hypothesis Tesmentioning
confidence: 81%
See 1 more Smart Citation
“…However, the mutant pigment at pH 4.4, 4.8, 5.5, 6.2, 6.4, 6.6, 7.2, 7.5, 7.8, 8.6, and 11.4 shows identical absorption spectrum to that at pH 6.6 (results not shown). Thus, the various levels of acid treatment suggest that there is no change in its protonation state that influences the electrostatic environment of the chromophore (26). At present, it is not clear why the absorption spectrum of the mutant pigment is broader than that of the UV pigment.…”
Section: Molecular Evolution Of the Avian Uv Pigments: Hypothesis Tesmentioning
confidence: 81%
“…The amino acid site 84 is located near the Schiff base nitrogen and E107 (corresponds to E113 of the bovine rhodopsin), counterion of the Schiff base (12,26,30). Using bovine rhodopsin, it has been suggested that one or a few water molecules is located in this region (31)(32)(33)(34).…”
Section: Molecular Evolution Of the Avian Uv Pigments: Hypothesis Tesmentioning
confidence: 99%
“…This result implied that there might be other amino acid residues determining the color regulation because it is quite conceivable that the change in the environment around the chromophore is one of the most influential factors regulating color. In fact, Sakmar and co-workers (26,27) succeeded in producing a significant blue shift for rhodopsin (500 nm) to 438 nm by simultaneous substitution of nine sites around the chromophore of rhodopsin, whose shift amounts to 80% of the spectral tuning between rhodopsin and the blue cone pigment. Therefore, it is considered that the max among archaeal rhodopsins is also determined by the difference in the environment around the chromophore.…”
mentioning
confidence: 99%
“…Mutagenesis experiments at this site in a variety of pigments have shown that A292S or S292A mutants demonstrate substantial blue and red spectral shifts, respectively (8,(12)(13)(14)(15)(16). As shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…This amino acid substitution red-shifts the max of the Drosophila Rh1 pigment and reciprocally blue-shifts the max of Rh6 pigment. Interestingly, this site also affects the spectral tuning of vertebrate pigments and corresponds to Ala-292 in bovine rhodopsin (8,(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%